What's so great about Christianity - D'Souza, Dinesh, 1961- (Washington, DC : Regnery Pub., 2007)
Examines the assumptions of Christianity and atheism, and argues, among other issues, that Christianity explains what modern science tells us about the universe and our origins better than atheism.
Preface: A challenge to believers--and unbelievers -- pt. 1: The future of Christianity. The twilight of atheism : the global triumph of Christianity -- Survival of the sacred : why religion is winning -- God is not great : the atheist assault on religion -- Miseducating the young : saving children from their parents -- pt. 2: Christianity and the West. Render unto Caesar : the spiritual basis of limited government -- The evil that I would not : Christianity and human fallibility -- Created equal : the origin of human dignity -- pt. 3: Christianity and science. Christianity and reason : the theological roots of science -- From logos to cosmos : Christianity and the invention of invention -- An atheist fable : reopening the Galileo case -- pt. 4: The argument from design. A universe with a beginning : God and the astronomers -- A designer planet : man's special place in creation -- Paley was right : evolution and the argument from design -- The Genesis problem : the methodological atheism of science -- pt. 5: Christianity and philosophy. The world beyond our senses : Kant and the limits of reason -- In the belly of the whale : why miracles are possible -- A skeptic's wager : Pascal and the reasonableness of faith -- pt. 6: Christianity and suffering. Rethinking the Inquisition : the exaggerated crimes of religion -- A license to kill : atheism and the mass murders of history -- pt. 7: Christianity and morality. Natural law and divine law : the objective foundations of morality -- The ghost in the machine : why man is more than matter -- The imperial "I" : when the self becomes the arbiter of morality -- Opiate of the morally corrupt : why unbelief is so appealing -- The problem of evil : where is atheism when bad things happen? -- pt. 8: Christianity and you. Jesus among other gods : the uniqueness of Christianity -- A foretaste of eternity : how Christianity can change your life.
Includes bibliographical references (p. [307]-334) and index
Keywords: Christianity -- Essence, genius, nature